A large hymenal polyp in a 21-year-old virgin - Borko, Elko (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2009)
Pathological conditions of the hymen are rare in everyday medical practice. They are usually encountered in the pediatric patient population and are sometimes a matter of forensic interest. We report an interesting case of a large hymenal polyp in an adolescent virgin that presented only a cosmetic problem. The polyp was excised, the hymenal ring was preserved, and the sample was histologically verified.
Keywords: deviška kožica; diagnostika; Himen; Hymen; Kirurgija; pathology; Patologija; Polipi; Polyps; surgery; vulva